ATM deficiency augments constitutively nuclear cyclin D1-driven genomic instability and lymphomagenesis - Vaites, LP (2013)
Cyclin D1 deregulation is implicated in the genesis of multiple human cancers. Importantly, nuclear cyclin D1 retention during S-phase promotes DNA re-replication and subsequent genomic instability, providing a direct correlation between aberrant cyclin D1/CDK4 activity, transcriptional regulation and double strand DNA break (DSB) induction. Together, these molecular events catalyze the genomic instability necessary for neoplastic transformation. Given that replication-associated DNA damage is central to cyclin D1-driven neoplasia, inactivation of critical checkpoint mediators should augment cyclin D1-dependent tumorigenesis in vivo. To interrogate potential synergy between constitutively nuclear cyclin D1 expression and impaired DSB-induced checkpoint integrity, Ataxia Telangiectasia Mutated (ATM)-deficient mice harboring the Eμ-D1T286A transgene were generated and evaluated for tumor onset. Eμ-D1T286A/ATM −/− mice exhibit dramatically accelerated incidence of both B- and T-cell lymphomas relative to Eμ-D1T286A or ATM −/− control cohorts. Lymphomas exhibit clonal chromosomal alterations distinct from ATM −/− mice, which typically acquire translocations involving the Tcrα/δ locus during V(D)J recombination, and instead harbor alterations at the c-Myc locus. Collectively, these findings reveal an intricate relationship wherein nuclear cyclin D1/CDK4 drives genomic instability in the absence of ATM function and clonal selection of cells harboring alterations within the murine c-Myc locus, ultimately facilitating transformation and tumor formation.